Implementing Intellectual Property Provisions in New-Generation Free Trade Agreements in the EU - Nam, Do Giang (VNU Journal of Science: Legal Studies; Vol 38 No 3, 2022)
The inclusion of chapters that introduce a high standard of intellectual property protection in free trade agreements has become an essential feature of the international commercial policy of developed countries. Based on the analysis of the legal policies and practices of entering into and implementing commitments on intellectual property in the new generation of free trade agreements of the European Union (EU), this article points out that there are two prominent legal aspects of implementing intellectual property provisions in the new generation of free trade agreements. On the one hand, in comparison to partners being developing countries, the EU has always been in the position of a negotiating party with a superior intellectual property protection system; therefore, the goal of these agreements is to provide “sticks and carrots” to push the developing countries to change their laws, policies, and standards. From the perspective of comparative law theory, the implementation of agreements will lead to the “transplantation and transformation” of intellectual property legislations from the EU to partner countries. On the other hand, in some typical cases related to i) the protection of genetic resources, traditional knowledge, and ii) technology transfer, the developing countries have also gained certain achievements in including the above issues in the agreements; and thereby imposing obligations on the EU to implement these commitments.